2013
DOI: 10.1080/09603123.2013.782605
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of foods for special diets produced in a school catering facility within a HACCP-based approach: a case study

Abstract: A study was carried out to verify the appropriateness of the Hazard Analysis and Critical Control Point (HACCP) plan adopted in a school catering facility. To that end, the microbiological quality of foods, the correct implementation of special diets (lactose- and gluten-free) and the nutritional value of foods were assessed. Thirty-six samples of lactose-free and 87 samples of gluten-free special diet food preparations were subjected to microbiological, chemical, and nutritional analyses. The data collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Microbiological analyses are an important tool to collect data to be used for the development and verification of an HACCP plan [1,11,12,13,14] as well as to assess the effectiveness of sanitation operations, to evaluate the compliance of incoming ingredients with safety criteria, and to determine the safety of end products [15]. In addition to these operations, periodic audits can be undoubtedly useful to examine the application of all control measures foreseen by an HACCP plan [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological analyses are an important tool to collect data to be used for the development and verification of an HACCP plan [1,11,12,13,14] as well as to assess the effectiveness of sanitation operations, to evaluate the compliance of incoming ingredients with safety criteria, and to determine the safety of end products [15]. In addition to these operations, periodic audits can be undoubtedly useful to examine the application of all control measures foreseen by an HACCP plan [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Data collected in the study by Petruzzelli et al [39] also revealed the appropriateness of the Hazard Analysis and Critical Control Point (HACCP) system to reduce the risk of gluten contamination in a school catering facility. The authors found only one sample out of 87 with gluten content above 20 ppm (1.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Although many countries adopt the Codex threshold, most lack a consistent monitoring process to evaluate gluten content in food [ 9 ]. Moreover, very few studies have been conducted to evaluate strategies to prevent gluten cross-contamination in food services [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%